IPTEK BAGI MASYARAKAT INDUSTRI KECIL ROBOT LINE FOLLOWER DI KELURAHAN WEDOMARTANI KABUPATEN SLEMAN - Erwan Eko Prasetiyo; You She Melly Anne Dharasta (Universitas Muhammadiyah Semarang, 2017)
The number of competing robot line follower events provide business opportunities for making robot line follower for the community especially in Sleman District, Special Region of Yogyakarta Province. In carrying out its business, partners have financial administration issues and bookkeeping. Partners also have production process issues. Partners don’t have a laser cutting machine to print the chassis (the main part of the robot) and often the lack of raw materials can lead to the late production of robots. Partners also have not been able to increase sales turnover due to lack of promotion. The purpose of this activity to help overcome the problems faced by both partners. The method undertaken is to perform improvement steps in the field of management, especially the production process, the field of production and marketing. Problem solving in the field of management is done by holding financial / book administration training for both partners. Solving problems in the field of production is done by the procurement of laser cutting machines, adding production space and toolset and the addition of electric power of 1,300VA to support production.Solving marketing problems is done by increasing promotion through publications through newspapers and brochures. Activities that have been implemented, among others: (1) Observation Products and Financial Administration System and Bookkeeping; (2) Training of Financial Administration System and Bookkeeping;(3) Establish System to Help the Production Process; (4) Assisting the Supply of Raw Materials and Production Facilities; And (5) Helping Promotion.Keywords: small industry, production, robot, line follower.